Biological Aspects of Sphyraena sphyraena (L., 1758) in the Central Mediterranean (E. Ionian Sea) - Vasiliki Nikiforidou; Aikaterini Anastasopoulou; Vasileios Xenikakis; Chryssi Mytilineou (Hydrobiology)
S. sphyraena is a widely distributed species with low commercial value and no sufficient scientific knowledge of its biology. In the present study, the age, growth, weight–length relationship, otolith morphometry, and reproduction of the species were investigated in the Eastern Ionian Sea for the first time. The von Bertalanffy growth function parameters were L∞ = 63.65 cm, k = 0.14 year−1 and t0 = −2.01 years and Φ′ = 2.75. The negative allometric growth in weight was found. Slope b of the weight–length relationship was 2.634. For the otolith moprhometry, the variables radius, length, width, area, perimeter, roundness, circularity, form factor, rectangularity, and ellipticity were examined, which showed that the otolith shape is elongated with an elliptical and rectangular form. Six otolith variables (radius, length, width, area, perimeter, and ellipticity) showed a significant relationship with size. The sex ratio (females/males) was 1:0.74 (no statistically significant difference from 1:1), and the spawning season extended from April to June with peak values of GSI in May for females and April for males. The results of this work improve our knowledge of the species life cycle and provide basic information for species stock identification and fisheries management.